The Impact of Logistics Integration on Supply Chain Performance: The Moderating Role of Information Sharing - Asare, Gabriel (International Journal of Supply Chain and Logistics, 2024)
Purpose: The study aims to assess the influence of logistics integration on supply chain performance, as well as the function of information sharing plays in that connection among supply chain partners in a vital section of Ghana's economy (the Energy Sector). Methodology: The study employed quantitative approach and adopted the explanatory research designs in the investigation. The research population targets senior management staff of energy firms operating within the Greater Accra Region. The study used convenience sampling approach to select a total of 111 employees from the population. Structured survey questionnaire was used as a data collection instrument to gather primary data from respondents. Data technique used were descriptive and inferential analysis and structural equation modelling using IBM SPSS (version 26) and Amos version 23. Findings: The study found that: a) logistics integration has a significant and positive effect on supply chain performance; b) information sharing correlates positively and significantly with supply chain performance; c) information sharing does not have any influence of the relationship between supply chain performance and logistics integration. Unique Contribution to Theory, Policy, and Practice: The study recommends that, supply chain managers to utilize technology as part of the strategic objectives to attain supply chain performance across their operations and lastly, managers are encouraged to promote successful information flow across the chain using design for disassembly principles, source effective communication, and supplier need-to-know policies. The study concludes that future studies are urged to create a research model that takes into account the comprehensive definition of sustainability, including its economic, social, and environmental elements, in order to fill in gaps in the literature and fill them. Future research is also urged to take into account how industrial innovation mediates the link between sustainability and other important outcome variables including sustainability performance, cost performance, customer happiness, and environmental performance.